CRMP1 and CRMP2 have synergistic but distinct roles in dendritic development. (2nd August 2016) - Makihara, Hiroko; Nakai, Shiori; Ohkubo, Wataru; Yamashita, Naoya; Nakamura, Fumio; Kiyonari, Hiroshi; Shioi, Go; Jitsuki‐Takahashi, Aoi; Nakamura, Haruko; Tanaka, Fumiaki; Akase, Tomoko; Kolattukudy, Pappachan; et al.
Abstract : Collapsin response mediator protein 2, CRMP2, has been identified as an intracellular signaling mediator for Semaphorin 3A (Sema3A). CRMP2 plays a key role in axon guidance, dendritic morphogenesis, and cell polarization. It has been also implicated in a variety of neurological and psychiatric disorders. However, the in vivo functions of CRMP2 remain unknown. We generated CRMP2 gene‐deficient ( crmp2 −/− ) mice. The crmp2 −/− mice showed irregular development of dendritic spines in cortical neurons. The density of dendritic spines was reduced in the cortical layer V pyramidal neurons of crmp2 −/− mice as well as in those of sema3A −/− and crmp1 −/− mice. However, no abnormality was found in dendritic patterning in crmp2 −/− compared to wild‐type ( WT ) neurons. The level of CRMP1 was increased in crmp2 −/−, but the level of CRMP2 was not altered in crmp1 −/− compared to WT cortical brain lysates. Dendritic spine density and branching were reduced in double‐heterozygous sema3A +/− ; crmp2 +/− and sema3A +/− ; crmp1 +/− mice. The phenotypic defects had no genetic interaction between crmp1 and crmp2 . These findings suggest that both CRMP1 and CRMP2 mediate Sema3A signaling to regulate dendritic spine maturation and patterning, but through overlapping and distinct signaling pathways. Abstract : In vitro finding suggests that both CRMP1 and CRMP2 are downstream molecules of Sema3A signaling. Dendritic spine density and branching were reduced in double‐heterozygous sema3A +/− ; crmp2 +/− and sema3A +/− ; crmp1 +/− mice, but the phenotypic defects had no genetic interaction between crmp1 and crmp2 . These findings suggest that both CRMP1 and CRMP2 mediate Sema3A signaling to regulate dendritic spine maturation and patterning, but through overlapping and distinct signaling pathways.